Midterm Outcome of Laparoscopic Sleeve Gastrectomy in Asians: a Systematic Review and Meta-analysis - Veeravich Jaruvongvanich (2020)
© 2019, Springer Science+Business Media, LLC, part of Springer Nature. Background: Laparoscopic sleeve gastrectomy (LSG) is a commonly performed bariatric surgery. Studies have suggested that LSG can provide effective and sustainable weight loss although most of them were conducted in Western populations. Our aim was to characterize the midterm outcome of LSG in Asians with obesity. Methods: MEDLINE and EMBASE were searched through August 2019 for studies that reported % total body weight loss (TBWL) and/or % excess weight loss (EWL) at 3 and/or 5 years among adult Asians with obesity who underwent LSG. Data on complications and surgical revision rate were also extracted. The pooled effect size and 95% confidence interval (CI) were calculated using a random effects model. Results: A total of 19 studies involving 6235 patients were included. The pooled mean %EWLs were 72.6% (95% CI 67.2–78.0, I2 = 97%); 67.1% (95% CI 61.7–72.6, I2 = 95%); and 59.1% (95% CI 48.8–69.4, I2 = 94%) at 1, 3, and 5 years, respectively. The pooled mean %TBWLs were 32.1%, 29.0%, and 25.5% at 1, 3, and 5 years, respectively. The pooled rates of revision due to gastroesophageal reflux disease and weight regain were 1.9% and 2.5%, respectively. Conclusions: Our meta-analysis suggests that LSG is an effective procedure for weight reduction that offers durable response for up to 5 years among Asians with obesity. The longer-term data is needed.